Thinking About Multiword Constructions: Usage‐Based Approaches to Acquisition and Processing. (24th February 2017) - Ellis, Nick C.; Ogden, Dave C.
Abstract: Usage‐based approaches to language hold that we learn multiword expressions as patterns of language from language usage, and that knowledge of these patterns underlies fluent language processing. This paper explores these claims by focusing upon verb–argument constructions (VACs) such as "V(erb) about n(oun phrase)." These are productive constructions that bind syntax, lexis, and semantics. It presents (a) analyses of usage patterns of English VACs in terms of their grammatical form, semantics, lexical constituency, and distribution patterns in large corpora; (b) patterns of VAC usage in child‐directed speech and child language acquisition; and (c) investigations of VAC free‐association and psycholinguistic studies of online processing. We conclude that VACs are highly patterned in usage, that this patterning drives language acquisition, and that language processing is sensitive to the forms of the syntagmatic construction and their distributional statistics, the contingency of their association with meaning, and spreading activation and prototypicality effects in semantic reference. Language users have rich implicit knowledge of the statistics of multiword sequences. Abstract : Ellis & Ogden examine the acquisition, processing and usage of verb‐argument constructions in English. They analyze the semantic, grammatical and distributional features of these multiword constructions in a large corpus; describes their use by both L1 and L2 learners; and reviews psycholinguistic findings on their processing by native and non‐native speakers. The findings demonstrate that language users have rich implicit statistical knowledge of multiword patterns and use this knowledge in learning and processing.